Research and Design of Chinese Dragon Based on OpenScad - Guo, Zefei (Transactions on Computer Science and Intelligent Systems Research, 2024)
OpenSCAD, an open-source 3D modeling software, has been widely favored by creators for its powerful functions and flexible scalability. Although OpenSCAD has a wide range of applications in the field of 3D modeling, there are still few studies on how to use it to build animated models with specific cultural characteristics. As one of the important symbols of traditional Chinese culture, the Chinese dragon has unique morphology and cultural connotation. Therefore, we hope to provide new ideas and methods for related fields by studying the application of OpenSCAD in building animated models of the Chinese dragon.This study mainly explored the process of using OpenSCAD, an open-source 3D modeling software, to construct animated models with Chinese cultural characteristics - the Chinese dragon. In the modeling process, we adopted a block-based modeling strategy, dividing the overall structure of the dragon into several main parts: head, body, claws, and tail. For each part, we fully utilized the basic primitive construction and transformation functions provided by OpenSCAD for fine shaping. Through this study, we successfully used OpenSCAD to construct an animated model of the Chinese dragon with distinct Chinese cultural characteristics. This achievement not only demonstrates the powerful functions and flexibility of OpenSCAD in modeling complex shapes, but also provides new ideas and methods for related fields.